COMPARISON OF FUNCTIONAL PROPERTIES OF HEMOLYMPH PROTEIN FROM FRESHWATER CRAB, BARYTELPHUSA CUNICULARIS WITH CASEIN, EGG ALBUMIN AND BOVINE SERUM ALBUMIN - D. PAGARE , SIDHARTH; E. R. MARTIN (The Bioscan, 2013)
The physico chemical and functional properties of hemolymph protein ( HP) from freshwater crab, Barytelphusa cunicularis was compared with commercially available proteins viz. Casein, egg albumin and Bovine serum albumin ( BSA) for possible use in food technology. The percentage solubility of proteins, observed were casein>HP>egg albumin>BSA at different pH. The emulsifying properties of casein, egg albumin, BSA and HP at pH 7 and 9,did not show any statistically significant difference. But, when compared with pH 7 and 9 between the groups, a statically significant difference was observed. The foam stability and capacity studies of protein were found in the order of casein> egg albumin=BSA>HP and casein<egg albumin<HP<BSA respectively. The foam stability and time showed a statistically significant relationship. The HP showed a less water binding capacity (WBC) and oil binding capacity (OBC) when compared to casein, BSA and egg albumin. Thus, the present study suggest suggests that HP is a good candidate for use in food processing industries and this protein should not be simply ignored.